Chlamydia Trachomatis Infection and Spontaneous Abortion: Infeksi Chlamydia Trachomatis dan Abortus Spontan - Rahayu Basir; Eddy Hartono; Eddy R. Moeljono; St. Nur Asni (Indonesian Journal of Obstetrics and Gynecology, 2021)
Abstract Objective: To determine the correlation between spontaneous abortion and Chlamydia trachomatis infection. Methods: A cross-sectional study was conducted in women who experienced spontaneous abortion. Normal pregnancies with gestational age more than equal to 37 weeks as control. Detection of C. trachomatis in the product of conception or placenta from curettage using the PCR method. Results: Positive C. trachomatis was found 3 cases in the abortion group and 4 cases in control. In the abortion group, C. trachomatis found in 1 case with vaginal discharge history and 2 cases without this history. C. trachomatis also found in 3 cases without a history of abortion. This bacteria was not found in patients with an abortion history. In the control group, 2 cases of positive C. trachomatis were found in pregnant women with or without a history of vaginal discharge and abortion, respectively. There were no significant differences regarding the positive of C. trachomatis between the two study groups regarding history of vaginal discharge and abortion. Conclusions: Spontaneous abortion does not correlate with C. trachomatis infection. Keywords: chlamydia trachomatis, infection, spontaneous abortion. Abstrak Tujuan: Untuk mengetahui hubungan antara abortus spontan dan infeksi Chlamydia trachomatis. Metode: Penelitian potong lintang dilakukan pada perempuan yang mengalami abortus spontan. Kehamilan normal dengan usia kehamilan lebih dari sama dengan 37 minggu sebagai kontrol. Deteksi C. trachomatis pada produk konsepsi atau plasenta dari kuretase menggunakan metode PCR. Hasil: C. trachomatis positif ditemukan 3 kasus pada kelompok aborsi dan 4 kasus dalam kontrol. Pada kelompok abortus spontan, C. trachomatis ditemukan pada 1 kasus dengan riwayat keputihan dan 2 kasus tanpa riwayat keputihan. C. trachomatis juga ditemukan pada 3 kasus tanpa riwayat abortus. Bakteri ini tidak ditemukan pada pasien dengan riwayat abortus. Pada kelompok kontrol, 2 kasus positif C. trachomatis masing-masing ditemukan pada perempuan hamil dengan atau tanpa riwayat keputihan dan abortus. Tidak ada perbedaan signifikan C. trachomatis positif antara kedua kelompok penelitian berdasarkan riwayat keputihan dan abortus. Kesimpulan: Abortus spontan tidak berkorelasi dengan infeksi C. trachomatis. Kata kunci: abortus spontan, chlamydia trachomatis, infeksi.